III-V nanowires for optoelectronic applications - Tan, H; Jiang, N; Saxena, D; Lee, Y; Mokkapati, S; Fu, L; Gao, Q; Joyce, H; Jagadish, C (Electrochemical Society Inc., 2013)
We present an overview of our work on improving the crystal quality and carrier lifetimes of our GaAs-based nanowires. These two properties are crucial for optoelectronic device applications and which we report by showing two examples of nanowire lasers and nanowire solar cells. © The Electrochemical Society.